Therapeutic and legal aspects of psilocybin in cancer-related depression - Wierzbicka, Małgorzata; Kopczyk, Renata; Gerlach, Aleksandra; Rymaszewska, Joanna (Frontiers in Psychiatry, 2025)
Depression prevalence is markedly elevated in oncological patients, particularly among head and neck cancer (HNC) cohorts, who face twice the prevalence of major depressive disorder (MDD) compared to other cancer populations. MDD in this context independently predicts poorer clinical outcomes and increased morbidity. HNC management often involves acute surgical interventions with disfiguring effects, creating a narrow therapeutic window for conventional antidepressants requiring weeks to achieve efficacy. Psychological interventions face similar time constraints, complicating perioperative mental health support. Psilocybin – metabolized to psilocin – modulates serotonin (5-HT2A) and dopamine receptors, demonstrating rapid antidepressant effects within hours rather than weeks. Clinical trials validate its superiority over escitalopram in MDD treatment and efficacy in PTSD and treatment-resistant depression. Despite these benefits, no studies explore perioperative applications in HNC patients. Psilocybin lacks international scheduling under UN conventions, permitting variable national policies: Australia - MDMA/psilocybin prescriptions (2023), USA - Insurance billing codes (2024), Portugal - Decriminalized, South Africa - Prescription medicine. In Polish Context psilocybin remains restricted to research settings, classified as a Group I-P substance under the 1971 Psychotropic Convention. This legal framework complicates clinical implementation despite emerging evidence of therapeutic potential. The critical challenge lies in reconciling psilocybin’s rapid antidepressant properties with regulatory barriers, particularly for HNC patients requiring immediate psychiatric support post-surgery. Interdisciplinary collaboration between oncologists, psychiatrists, and policymakers is essential to design ethical clinical pathways under current legislative constraints.